Life's golden ticket : a story about second chances - Burchard, Brendon (HarperOne, 2016)
The narrator's dying fiancée sends him to an abandoned amusement park where, with his host, Henry, he begins a journey of self-discovery filled with allegorical amusement park rides and wise carnies.